LeHaMoC: Leptonic-Hadronic Modeling Code for high-energy astrophysical sources - Stathopoulos, S. I.; Petropoulou, M.; Vasilopoulos, G.; Mastichiadis, A. (Astrophysics Source Code Library, 2024)
LeHaMoC simulates high-energy astrophysical sources. It simulates the behavior of relativistic pairs, protons interacting with magnetic fields, and photons in a spherical region. The package contains numerous physical processes, including synchrotron emission and self-absorption, inverse Compton scattering, photon-photon pair production, and adiabatic losses. It also includes proton-photon pion production, proton-photon (Bethe-Heitler) pair production, and proton-proton collisions. LeHaMoC can model expanding spherical sources with a variable magnetic field strength. In addition, three types of external radiation fields can be defined: grey body or black body, power-law, and tabulated.
Keywords: Software